A look into the cockpit of the developing locust: Looming detectors and predator avoidance. Issue 11 (8th May 2014) - Sztarker, Julieta; Rind, F. Claire
ABSTRACT For many animals, the visual detection of looming stimuli is crucial at any stage of their lives. For example, human babies of only 6 days old display evasive responses to looming stimuli (Bower et al. [1971]: Percept Psychophys 9: 193–196). This means the neuronal pathways involved in looming detection should mature early in life. Locusts have been used extensively to examine the neural circuits and mechanisms involved in sensing looming stimuli and triggering visually evoked evasive actions, making them ideal subjects in which to investigate the development of looming sensitivity. Two lobula giant movement detectors (LGMD) neurons have been identified in the lobula region of the locust visual system: the LGMD1 neuron responds selectively to looming stimuli and provides information that contributes to evasive responses such as jumping and emergency glides. The LGMD2 responds to looming stimuli and shares many response properties with the LGMD1. Both neurons have only been described in the adult. In this study, we describe a practical method combining classical staining techniques and 3D neuronal reconstructions that can be used, even in small insects, to reveal detailed anatomy of individual neurons. We have used it to analyze the anatomy of the fan‐shaped dendritic tree of the LGMD1 and the LGMD2 neurons in all stages of the post‐embryonic development of Locusta migratoria. We also analyze changes seen during the ontogeny of escape behaviors triggered by looming stimuli, specially the hiding response. © 2014 Wiley Periodicals, Inc. Develop Neurobiol 74: 1078–1095, 2014